2016
DOI: 10.1080/03630242.2016.1150387
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in women in relation to occupational status

Abstract: Through this cross-sectional study the authors explore urinary incontinence in women in relation to occupational status and environment. Data from the fourth Korea National Health and Nutrition Examination Survey (2008-2009) were used (n = 5,928) excluding those aged under 19 or over 65 years, male, with renal disease, and with missing data. Urinary incontinence was prevalent in working women. Compared to unemployed women, the adjusted odds ratio (95% confidence intervals) for women working in services/sales w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 43 publications
0
48
1
Order By: Relevance
“…Of the eight publications that evaluated broader occupational groups, three studies reported prevalence rates (two reported UI and one OAB) across occupational groups . In multivariable analyses from two of the three studies, women working in manual labor jobs had an increased odds of UI (OR 6.9, 95%CI 5.7‐8.5) and OAB (OR 1.7, 95%CI 1.6‐1.8) compared to women in non‐manual occupations or unemployed women .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the eight publications that evaluated broader occupational groups, three studies reported prevalence rates (two reported UI and one OAB) across occupational groups . In multivariable analyses from two of the three studies, women working in manual labor jobs had an increased odds of UI (OR 6.9, 95%CI 5.7‐8.5) and OAB (OR 1.7, 95%CI 1.6‐1.8) compared to women in non‐manual occupations or unemployed women .…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40][41][42][43] Of the eight studies that compared women across broad occupation groups, the authors reported specific occupation types as employed versus non-employed, paid versus non-paid, and manual versus non-manual. [13][14][15]20,[44][45][46] One of the eight examined occupation type as manual, non-manual, sales/ service versus unemployed. 13 Studies also varied in the type of bladder symptoms reported, the frequency of the symptom recorded, and the use of validated measures to ascertain symptoms (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations